Learning by doing and creation of the shared discovery curriculum. Issue 1 (31st December 2023) - Sousa, Aron; Mavis, Brian; Laird-Fick, Heather; DeMuth, Robin; Gold, Jonathan; Emery, Matthew; Ferenchick, Gary; Paganini, Anthony; Colon-Berlingeri, Migdalisel; Arvidson, Cindy; Toriello, Helga; Parker, Carol; et al.
ABSTRACT: Background: The Michigan State College of Human Medicine began as an experiment to teach medical students in community-based settings and to create a primary care workforce for the state. Decades later, CHM faced internal and external challenges that spurred creation of a new curriculum – the Share Discovery Curriculum – founded on learning by doing and other learning theories. Methods: A curricular design group (CDG) developed guiding principles for reform. Based on this, pedagogies and structures were selected to achieve this vision and developed into a curricular structure. Components of the first-year curriculum were piloted with a group of students and faculty members. Results: Six guiding principles were endorsed, grounded in learning theories such as Dewey's Learning by Doing. Based upon these, several key features of the new curriculum emerged: learning communities; one-on-one coaches for students; symptom-based presentations for content; simulation, authentic clinical tasks, flipped classrooms, and modified practice-based learning as primary teaching modalities; early, integrated clinical and scientific learning; milestones as course learning objectives; and a multidimensional, competency-based assessment system. Discussion: The process and outcomes described here are intended as an exemplar for schools undertaking curricular change. Early stakeholder engagement, faculty development, sustainable administrative systems, and managing complexity are core to the success of such endeavors.